“Estudio y diseño del sistema de alcantarillado sanitario y pluvial para las comunidades de Shagal y río Blanco del cantón Camilo Ponce Enríquez- provincia del Azuay” - Rivera Morán, Jenner Eduardo (2015)
The lack of systems sanitary and storm sewer system with a treatment plant wastewater suffers and complicates the quality of life of the inhabitants of the communities of Shagal and Rio Blanco, the same as because of this need live in an unhealthy environment at the expense of contracting a number of diseases that undoubtedly are harmful to your health. Aware of this problem arises as main objective the development of studies and system designs sanitary, storm sewer and treatment plant wastewater, which will help improve the quality of life of the inhabitants of the area and the provision end of wastewater which is currently carried out. The results of the different research techniques and various field work such as surveys, topography, soil study, etc., are considered for calculation and design of systems that were detailed in the previous paragraph, which they will not only end the existing problems if not also help the social welfare of the community. The project itself, considered of vital importance for the development of these communities is a viable and sustainable level, whose purpose and design were reviewed and approved by experts in the field for later execution by any contracting entity.